From psychiatric hospitals to residential facilities: Characteristics of patients who benefited from an institutional partnership. (1st July 2022) - Stojanov, Thomas; Perquier, Florence; Boiteux, Catherine; Soudani, Martine Le Noc; Château, Naïssa; Perozziello, Anne; Gallarda, Thierry
Abstract: Objectives: The population of older adults is growing fast, especially in Europe and Northern America. Old age is often associated with mental health comorbidities. Moreover, life expectancy of people suffering from psychiatric disorders has increased, but with age‐related difficulties, such as loss of independence. This represents a challenge for public health policies, as this population requires specific care and living conditions. As a response, a convention was signed between living facilities for dependent elderly (EHPAD) and the GHU Paris Psychiatry and Neurosciences. The agreement included dedicated places in EHPAD for older patients with psychiatric disorders. The aim of the study was to describe the sociodemographic and clinical characteristics of those patients. Methods: We conducted a cross‐sectional study among patients who applied for an EHPAD admission. Results: Between 2016 and 2019, 163 patients applied for placement in an EHPAD, and 117 were admitted (72%). Applicants were 71 years old on average. Admitted patients were older than non‐admitted and lived in different Parisian sectors. Among admitted patients, nine in 10 were single, divorced or widowed, and 64.3% were childless. Almost half of them were schizophrenic or had delusional disorders (46.9%), and 65.3% were considered as moderately dependent. At the time of the study, 89 patients still lived in EHPAD. Almost half of them had anxiety and depressive disorders (48.3%), 19.1% had cognitive disorders, and 42.7% manifested agitation. Conclusions: Our study highlighted older psychiatric patients' specificities regarding their admission status into long‐term living facilities. Key points: Ageing adults who present with psychiatric disorders require specific care at older age. An agreement was signed in 2016 between Parisian psychiatric hospitals and residential facilities for dependent elderly people (EHPAD) to provide appropriate living conditions and care for ageing patients with chronic psychiatric disorders. Almost three out of four applicants were admitted in an EHPAD (72%). Among rejected applications, more than one‐third (35%) were related to administrative issues. Psychiatric patients who applied to EHPAD through the convention were younger than the other residents (71 vs. 85 years old), less dependent, and had less frequently cognitive disorders.